Pengembangan Model BIMA (Budaya, Inkuiri, Mencipta, Aktif) dalam Pembelajaran Menulis Narasi - Nita Anjung Munggaran; Yeti Mulyati; Vismaia S. Damayanti; Dadang S. Anshori (Aksara, 2025)
This study aims to analyze the needs and test the effectiveness of the BIMA (Culture, Inquiry, Creation, and Activity) model in strengthening cultural literacy and improving students' narrative writing skills in higher education. The method used was Research and Development (R&D) with four stages: exploration, prototype design, field trials, and final validation and model revision. Data were obtained through focus group discussions, questionnaires, observations, interviews, and document analysis. Instrument validity was tested through expert and student validation, and qualitative data validity was strengthened through source triangulation and informant review. Quantitative data were analyzed descriptively, while qualitative data were analyzed using the Miles and Huberman interactive model. The results showed that the BIMA model significantly improved students' narrative writing skills by strengthening cultural literacy. The average assessment from the three student groups was categorized as "very important" with a score of 4.38, confirming the model's suitability for implementation in narrative writing instruction in higher education. The implications of this research indicate that the BIMA model can be an alternative for contextual and character-based learning, in line with the principles of Freedom to Learn (Merdeka Belajar), and contribute to strengthening cultural literacy and developing students' national character. AbstrakPenelitian ini bertujuan untuk menganalisis kebutuhan serta menguji efektivitas model BIMA (Budaya, Inkuiri, Mencipta, Aktif) dalam penguatan literasi budaya untuk meningkatkan kemampuan menulis narasi mahasiswa di Perguruan Tinggi. Metode yang digunakan adalah Research and Development (R&D) dengan empat tahap, yaitu eksplorasi, perancangan prototipe, uji coba lapangan, serta validasi akhir dan revisi model. Data diperoleh melalui diskusi kelompok terarah, kuesioner, observasi, wawancara, dan analisis dokumen, dengan validitas instrumen diuji melalui validasi ahli dan mahasiswa, serta keabsahan data kualitatif diperkuat dengan triangulasi sumber dan tinjauan informan. Analisis data kuantitatif dilakukan secara deskriptif, sedangkan data kualitatif dianalisis menggunakan model interaktif Miles dan Huberman. Hasil penelitian menunjukkan bahwa model BIMA secara signifikan mampu meningkatkan kemampuan menulis narasi mahasiswa melalui penguatan literasi budaya. Rata-rata penilaian dari tiga kelompok mahasiswa menunjukkan kategori “sangat penting” dengan skor 4,38, yang menegaskan bahwa model ini layak diterapkan dalam pembelajaran menulis narasi di Perguruan Tinggi. Implikasi penelitian ini menunjukkan bahwa model BIMA dapat menjadi alternatif pembelajaran kontekstual dan berkarakter, sejalan dengan prinsip Merdeka Belajar, serta berkontribusi terhadap penguatan literasi budaya dan pembentukan karakter kebangsaan mahasiswa.